HOMOPHOBIA AND US - Wahyu Rahardjo (Jurnal Psikologi, 2009)
Homophobia is an interesting topic to be discussed not only because of its universality but also its controversion. Homophobia grows among the condition of misunderstanding and prejudice from heterosexism hegemony. Homophobia is more impressive to be felt because the shallow understanding of religion. On the other hand, only few people who realize that human sexual attitudes and behaviors is constructed by the culture. Learning processes that supposed to be done by heterosexuals about how to see the existance of gay wisely would help to simplify the problems.Keywords: homophobia, heterosexism